Impact of protein content and pH on the properties of microwaved, expanded, shelf-stable cheese puff snacks made from dairy powders - J.M. Pronschinske; S. Govindasamy-Lucey; J.J. Jaeggi; R.A. Ibáñez; M.E. Johnson; J.A. Lucey (Journal of Dairy Science, 2025)
ABSTRACT: Certain cheeses (e.g., Mozzarella) can be stretched and molded when heated. If a cheese can stretch, perhaps its properties can also be modified to allow it to expand during microwave heating and drying to produce a crunchy, shelf-stable snack. To investigate this concept, we made a model system similar to pasteurized process cheese product (PPCP) that allowed us to vary 2 key parameters; protein (PN) content and the pH value, and to limit the meltability due to the high levels of intact casein. Cylinders of PPCP were microwaved to try to produce shelf-stable cheese puffs. Nine different PPCP treatments were made (n = 3) in a process cheese cooker using micellar casein powder, anhydrous milkfat, lactose, maltodextrin (MD), NaCl, trisodium citrate (TSC), citric acid (CA), and water. The MD addition was used to vary the PN content of PPCP from 30% (0% MD), 24% (∼8.3% MD), and 20% (∼16.8% MD). The use of MD allowed us to keep the moisture content constant in all the treatments. The pH values were varied from 5.7, 5.4, and 5.0, and the experimental design was a 3 × 3 factorial design of 3 PN levels and 3 pH levels. Ingredients were mixed in the process cheese cooker and then heated to 82°C for 2 min. All PPCP samples exhibited no melting (i.e., loss tangents <1) during heating when measured by small-strain oscillatory rheology. Buffering curves of the PPCP indicated that little of the indigenous colloidal calcium phosphate remained in the PPCP due to the addition of TSC and CA. After preliminary investigation, we found that expanded cheese could be formed from cylinders (9 mm in height × 13 mm in diameter) that were cut from PPCP and heated in a 900-W homestyle microwave oven for 45 to 70 s. These expanded puffs had a water activity of 0.24 ± 0.05. The puffs made from 30% PN samples expanded more (expansion of ∼440%) compared with the puffs made from 24% PN or 20% PN samples (expansions of ∼260% and ∼210%, respectively) when measured by glass bead displacement. In contrast, expansion was not significantly affected by the pH value of the PPCP base. After 1 wk of storage at room temperature, cheese puffs were evaluated by quantitative descriptive sensory analysis for textural attributes using trained panelists (n ≥8) based on a 15-point scale for texture. Crunchiness, tooth packing, and hardness attributes were lower for puffs made with 30% PN samples than the values for those made with 20% PN samples. Tooth cling, evaluated on a 6-point scale, was highest for puffs made with 20% PN samples (∼4.5). Puff texture was unaffected by the pH value. Scanning electron microscopy showed thicker cell walls for the puffs made from 24% and 20% PN samples when compared with 30% PN samples. Our model PPCP system could puff and expand, but the MD added to adjust (reduce) the PN content negatively affected expansion. The PN content of the PPCP was more important than the pH value for its expansion properties. A lack of melt during heating appeared to help facilitate expansion when PPCP was heated in a microwave.